C-MET inhibitors for advanced non-small cell lung cancer. (3rd April 2018) - Pasquini, Giulia; Giaccone, Giuseppe
ABSTRACT: Introduction : The role of the c-mesenchymal-epithelial transition factor (c-MET) signaling pathway in tumor progression and invasion has been extensively studied. C-MET inhibitors have shown anti-tumor activity in NSCLC both in preclinical and in clinical trials. However, given the molecular heterogeneity of NSCLC, it is likely that only a specific subset of NSCLC patients will benefit from c-MET inhibitors. Emerging data also suggest that MET inhibitors in combination with EGFR-TKIs (epidermal growth factor receptor tyrosine kinase inhibitors) may have a role in therapy for both EGFR-TKI resistant and EGFR-TKI naïve patients. The challenges ahead are in the identification of the molecular subtypes that benefit most. Areas covered : This review summarizes the current understanding of c-MET biology in relation to studies evaluating c-MET inhibitors in the treatment of NSCLC. Expert opinion : MET inhibitors have the potential to benefit subsets of NSCLC patients with specific genetic alterations. Exon-14 skipping mutations appear so far to be the most promising molecular subset that is sensitive to MET inhibitors, whereas overexpression, amplification and point mutations of MET seem more challenging subgroups to target. Combination with other target agents, such as EGFR inhibitors, may represent a promising therapeutic strategy in specific areas (e.g. EGFR-TKI resistance).